N-Encapsulation Maintain Yield of Rice (Oryza sativa L.) Under Drought Condition - Barunawati, Nunun; Wahyu, Dina; Sumardi, Sumardi (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2019)
An environment is strongly affected plant growth, particularly under drought condition. The obstacle for this condition can be maintained by water and nitrogen sources. The aim of this research was to determine and observe the effect of N-encapsulation on the distribution of macro nutrients in the vegetative and generative phases of rice plants (Oryza sativa L.) during rice growth. The difference of nitrogen sources will influence the nutrient absorption by roots. This research was conducted in June to September 2018 at field experiment in Batu, East Java, Indonesia. The method used a Randomized Block Design with the first factor was nitrogen sources and the second factor was field capacity as drought levels. The result showed that the proline content was 0.67 µm/g in plant treated by Urea which is higher and following by N-encapsulation at 0.52 µm/g. The proline strongly maintained grain-filling phases until field capacity 25 % at the entire nitrogen source (N-encapsulation, ZA, Urea) are 72.73 g; 69.93 g; and 66.15 g respectively. At 25 % field capacity induced length of roots and had the lowest number of tillers at 30.55 by N-encapsulation and less number of panicles was 19.33 per clump. The N accumulations were maintenance in higher concentration of leaves at 100 %field capacity compared with the other treatments.